PENGETAHUAN DAN SIKAP IBU TENTANG KONTRASEPSI SUNTIK DI RB SITIANA BARUS DESA NAMO BINTANG KEC.PANCUR BATU TAHUN 2015 - Yufdel Yufdel; Dina Indarsita; Hanna Laila Br Ginting (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2016)
Injection contraception is one of effective contraception method in which a method in its using has effectiveness or a higher survive and the lower rate of failure than the natural contraception. The objective of this research is to study knowledge and behavior of mothers about injection contraception at RB Sitiana Barus desa Namo Bintang subdistrict of Pancur Batu of 2015. This research applied descriptive study in order to depict the actual condition of knowledge and behavior of mother about injection contraception at RB Sitiana Barus desa Namo Bintang subdistrict of Pancur Batu of 2015. This research was conducted with the sample of 31 respondent by cross sectional design. The data was collected by questionnaire that consist of knowledge and behavior. Based on the result of research indicates that the knowledge of mother about injection contraception of 31 respondent with sufficient knowledge is 13 respondent (41.9%) and have the positive behavior for 30 respondent (96.8%). It is suggested to the medician in RB Setiana Barus to increase the health service.